Does bone mineral density change in polycystic ovarian syndrome? - Funda Dinc Elibol; Sezen Bozkurt Koseoglu (Medicine Science, 2019)
Polycystic ovarian syndrome (PCOS), is the most frequent endocrine disorder in reproductive age and PCOS has effects on bone metabolism. There is conflicting data on the effect of PCOS on bone metabolism. The aim of this study to evaluate whether bone mineral density (BMD) changes in PCOS or not. Twenty-seven patients with PCOS for the study group and 27 patients for the control group were included in this retrospective study. BMD measurements with abdomen CTs were taken for each lumbar vertebra (from vertebra L1 to vertebra L5) and sacral 1st vertebra. BMD measurements were recorded as HU. The lumbar 5th vertebras BMD was 238.70±47.80 HU in the PCOS group and 264.91±36.62 in the control group and the difference was statistically significant (P=0.033). BMD values of all vertebras were lower in the PCOS group than the control group, but statistically, significance was seen in only the lumbar 5th vertebra. BMD values were found to be lower in PCOS than the control group for all vertebras in this study. Even though there is no scanning method recommend to women in PCOS for BMD according to the current guidelines and literature, we think these patients should be evaluated more carefully in advanced ages in the light of the results of our study. [Med-Science 2019; 8(4.000): 792-5]